1978
DOI: 10.1172/jci109101
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aminoglutethimide on Blood Pressure and Steroid Secretion in Patients with Low Renin Essential Hypertension

Abstract: A B S T R A C T An inhibitor of adrenal steroid biosynthesis, aminoglutethimide, was administered to seven patients with low renin essential hypertension, and the antihypertensive action of the drug was compared with its effects on adrenal steroid production. In all patients aldosterone concentrations in plasma and urine were within normal limits before the study. Mean The gradual lowering of blood pressure and body weight during aminoglutethimide therapy is consistent with the view that the antihypertensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1981
1981
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 30 publications
2
6
0
Order By: Relevance
“…low renin levels in patients with resistant hypertension reflects a broader role of mineralocorticoid excess than indicated by measurement of aldosterone levels is likewise consistent with multiple studies over many decades supporting the concept of low-renin hypertension as a variation of aldosterone-induced hypertension (35)(36)(37)(38).…”
Section: Resistant Hypertension and Primary Aldosteronismsupporting
confidence: 81%
“…low renin levels in patients with resistant hypertension reflects a broader role of mineralocorticoid excess than indicated by measurement of aldosterone levels is likewise consistent with multiple studies over many decades supporting the concept of low-renin hypertension as a variation of aldosterone-induced hypertension (35)(36)(37)(38).…”
Section: Resistant Hypertension and Primary Aldosteronismsupporting
confidence: 81%
“…Our results with multidimensional response surface modeling that show the importance of aldosterone in control of salt-sensitive blood pressure changes as well as the laboratory investigations of Friedman and Jones provide an explanation for the depressor effects of aminoglutethimide reported by Woods et al 38 and Taylor et al 39 The cumulative results of the studies relating adrenal cortical abnormalities to hypertension are but another step in defining the role of the adrenal cortex, and they provide support for Dr. Corcoran's intuition of the importance of that role. In the 1951 report of low sodium diet therapy, after noting a lack of quantitative relation between sodium balance and arterial pressure changes, he commented: "Many facts point to a change in the function of the adrenal cortex or to a change in the response of vascular end organs to the effect of its hormones as the primary determinant of sodium responsiveness."…”
Section: Aldosterone As Determinant Of Salt-sensitive Hypertensionsupporting
confidence: 77%
“…37 There is, however, compelling evidence that aldosterone (or some salt-active steroid) features in "low renin" hypertension. Woods et al 38 found that administration of aminoglutethimide, an inhibitor of steroidogenesis, reduced pressure to normal in such patients, and this finding was later confirmed by Taylor et al 39 Also, in 1950 Davies and Clark 40 described an "endocrine hypertensive syndrome" in which a low sweat sodium was considered to reflect adrenal cortical overactivity.…”
Section: Mineralocorticoids and Hypertensionmentioning
confidence: 93%
“…Plasma renin activity is reported as nanograms antiotensin I per milliliter plasma per hour of incubation after a 3-hour incubation. 19 Plasma catecholamines were assayed by the radioenzymatic method of Da Prada and Yurcher 20 and reported as picograms per milliliter plasma. 21 was used to analyze the morphometric data, with multiple comparisons based on the Bonferroni inequality.…”
Section: Hormonal Assaysmentioning
confidence: 99%